2009
DOI: 10.1002/ptr.2942
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin inhibits fat accumulation in 3T3‐L1 adipocytes

Abstract: Shikonin, 5,6-dihydroxyfl avone-7-glucuronic acid, is the main ingredient of Lithospermum erythrorhizon Sieb. et Zucc, and was reported to have various biological activities including antiinfl ammatory, anticancer, antimicrobial and others. This study aimed to elucidate, for the fi rst time, the antiobesity activity of shikonin and its mechanism of action. Shikonin was found to inhibit fat droplet formation and triglyceride accumulation in 3T3-L1 adipocytes. The half inhibitory concentration, IC 50 , for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…PPAR-γ is considered a master regulator of adipocyte differentiation and, along with C/EBPα, regulates downstream target genes such as aP2 and lipoprotein lipase (LPL) (Rosen et al, 2002;Wu et al, 1999). Previous studies show that shikonin inhibits adipocyte differentiation in 3T3-L1 cells (Gwon et al, 2013;Lee et al, 2010Lee et al, , 2011, and we also found that shikonin downregulated PPAR-γ, C/EBPα, aP2, and FAS mRNA expression and protein content in white adipose tissue. These results suggest that shikonin reduced adipogenesis via decreased expression of adipogenic genes.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…PPAR-γ is considered a master regulator of adipocyte differentiation and, along with C/EBPα, regulates downstream target genes such as aP2 and lipoprotein lipase (LPL) (Rosen et al, 2002;Wu et al, 1999). Previous studies show that shikonin inhibits adipocyte differentiation in 3T3-L1 cells (Gwon et al, 2013;Lee et al, 2010Lee et al, , 2011, and we also found that shikonin downregulated PPAR-γ, C/EBPα, aP2, and FAS mRNA expression and protein content in white adipose tissue. These results suggest that shikonin reduced adipogenesis via decreased expression of adipogenic genes.…”
Section: Discussionsupporting
confidence: 48%
“…Shikonin has anti-adipogenic roles in vitro (Lee et al, 2010(Lee et al, , 2011, but whether it has an anti-obesity effect in vivo has not been investigated. To our knowledge, the present study is the first to assess the role of shikonin on body weight gain and its related metabolic pathways in vivo in an obese mouse model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shikonin also caused the accumulation of Pt-3,4,5-P3, the activation of protein kinase B, and inhibited several protein phosphatases in different cell systems. 150) Hyperglycemia and hyperlipidemia are prime identifying characteristics in the progression of type-2 DM and chronic cardiovascular disorders. 132) Insulin resistance, the main cause of type-2 DM is linked with the release of free fatty acids and proinflammatory cytokines from adipose tissues in subjects with obesity or excessive adiposity, which stimulates beta cells to over-secrete insulin and leads to a reduction in receptors.…”
Section: Antidiabetic Mechanisms Of Naphthoquinonesmentioning
confidence: 99%
“…It has also been reported that shikonin inhibits adipogenesis by both up-(SREBP1C) and downstream regulation (PPARγ and CCAAT/ enhancer binding protein alpha (C/EBPα)). 151) Various synthetic naphthoquinones have also been reported upon due to their antidiabetic potential. For example, 5,8-diacetyloxy-2,3-dichloro-1,4-naphthoquinone (48) was obtained through a screening of numerous chemical libraries, consisting of almost 4500 natural and synthetic molecules.…”
Section: Antidiabetic Mechanisms Of Naphthoquinonesmentioning
confidence: 99%